Evaluation of confirmatory data following the Article 12 MRL review and modification of the existing maximum residue levels for abamectin in various commodities. (23rd January 2020) - ,; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; Nave, Stefanie; et al.
Abstract: The applicant Syngenta Crop Protection submitted a request to the competent national authority in the Netherlands to evaluate the confirmatory data addressing information that was identified as not available for abamectin in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005. In addition, in accordance with Article 6 of Regulation (EC) No 396/2005, the applicant submitted a request to modify the existing MRLs for abamectin in lamb's lettuces, lettuces, escaroles, cresses and other sprouts/shoots, roman rocket/rucola, baby leaf crops, celery leaves, spinaches and similar leaves, beans with pods and peas with pods. The data gap on the validation for the enforcement analytical method was satisfactorily addressed; in addition, the requested residue trials to support the indoor winter use on lamb's lettuces were provided. For pome fruits and tomatoes, lower MRLs were derived based on alternative good agricultural practices (GAPs) already assessed by EFSA. Among the intended new uses requested in the MRL application, the residue data were sufficient to support an MRL proposal for the indoor winter use on lamb's lettuces and baby leaf crops, the outdoor Southern Europe use on lamb's lettuces, escaroles, cresses and other sprouts/shoots, roman rocket/rucola, baby leaf crops, spinaches and similar leaves, celery leaves and the indoor winter use on peas with pods. For lettuces and beans with pods, the supporting data were not fully compliant with the data requirements, and further risk management discussions are recommended to decide whether a modification of the existing MRLs would be appropriate. EFSA updated the most recent consumer risk assessment for abamectin and concluded that the long‐term dietary intake is unlikely to present a risk to consumer health. According to the internationally agreed methodology, an acute consumer risk was not identified in relation to the uses assessed.